Technology development of reuse in the real estate sector A case study of the implementation of CCBuild and its possible development to solve challenges with reuse in renovation projects - GAGNER-GEEBER, PONTUS; BERNTSSON, OSCAR (My University, 2023)
The transition of the construction industry toward circularity includes the reusage of materials, where technologies to simplify the process has recently been introduced to the market. The purpose of the study was to identify barriers and drivers of reuse and asses the development potential of the reuse technology, CCBuild, to enhance the process of reuse in renovation projects. The study is based on a qualitative research strategy including a literature review, interview study and a case study. The research has identified quality, financial, logistical and coordination as main areas of barriers and drivers to develop the work with reuse. The areas include issues related to communication, knowledge, and time aspects. Identified drivers were involving actors, enhanced design phase and streamlining. The proposals of improvements to CCBuild include enhanced user experience, cooperation with competitive technologies and continued work with cooperation within the sector. The study will contribute to increased awareness and knowledge of reuse and allow for a more effective transition to circularity with the help of reuse.
Keywords: Reuse, construction, technology, CCBuild, barriers, drivers